Morphological adaptation for ectosymbiont maintenance and transmission during metamorphosis in Lagria beetles - Janke, Rebekka S.; Moog, Safira; Weiss, Benjamin; Kaltenpoth, Martin; Flórez, Laura V. (Frontiers in Physiology, 2022)
The diversity and success of holometabolous insects is partly driven by metamorphosis, which allows for the exploitation of different niches and decouples growth and tissue differentiation from reproduction. Despite its benefits, metamorphosis comes with the cost of temporal vulnerability during pupation and challenges associated with tissue reorganizations. These rearrangements can also affect the presence, abundance, and localization of beneficial microbes in the host. However, how symbionts are maintained or translocated during metamorphosis and which adaptations are necessary from each partner during this process remains unknown for the vast majority of symbiotic systems. Here, we show that Lagria beetles circumvent the constraints of metamorphosis by maintaining defensive symbionts on the surface in specialized cuticular structures. The symbionts are present in both sexes throughout larval development and during the pupal phase, in line with a protective role during the beetle’s immature stages. By comparing symbiont titer and morphology of the cuticular structures between sexes using qPCR, fluorescence in situ hybridization, and micro-computed tomography, we found that the organs likely play an important role as a symbiont reservoir for transmission to female adults, since symbiont titers and structures are reduced in male pupae. Using symbiont-sized fluorescent beads, we demonstrate transfer from the region of the dorsal symbiont-housing organs to the opening of the reproductive tract of adult females, suggesting that symbiont relocation on the outer surface is possible, even without specialized symbiont adaptations or motility. Our results illustrate a strategy for holometabolous insects to cope with the challenge of symbiont maintenance during metamorphosis via an external route, circumventing problems associated with internal tissue reorganization. Thereby, Lagria beetles keep a tight relationship with their beneficial partners during growth and metamorphosis.